2008
DOI: 10.1016/j.jtcvs.2007.08.052
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane cuffed endotracheal tubes to prevent early postoperative pneumonia after cardiac surgery: A pilot study

Abstract: Polyurethane cuffed endotracheal tubes can reduce the frequency of early postoperative pneumonia in cardiac surgical patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
2
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 33 publications
4
87
2
6
Order By: Relevance
“…Cox regression analysis showed that polyvinyl cuffed tubes were a risk factor for global VAP (hazard ratio (HR) 3.3; = 0.001), early onset VAP (HR 3.3, = 0.02), and late onset VAP (HR 3.5; = 0.01). In addition, a prospective, single-blinded, randomized pilot study revealed that the PU-cuffed ETTs reduced the frequency of early postoperative pneumonia in cardiac surgical patients [18]. Our study, however, demonstrates a significant reduction of VAP incidence on a larger scale with a PU-cuffed ETT.…”
Section: Discussioncontrasting
confidence: 56%
“…Cox regression analysis showed that polyvinyl cuffed tubes were a risk factor for global VAP (hazard ratio (HR) 3.3; = 0.001), early onset VAP (HR 3.3, = 0.02), and late onset VAP (HR 3.5; = 0.01). In addition, a prospective, single-blinded, randomized pilot study revealed that the PU-cuffed ETTs reduced the frequency of early postoperative pneumonia in cardiac surgical patients [18]. Our study, however, demonstrates a significant reduction of VAP incidence on a larger scale with a PU-cuffed ETT.…”
Section: Discussioncontrasting
confidence: 56%
“…70,71,75,[85][86][87] Significantly reduced microaspiration has been reproduced in clinical trials, 75,78 coinciding with significant reductions in VAP (26 -45% relative decrease). [88][89][90] However, others have not been able to demonstrate the superiority of polyurethane-cuffed ETTs in reducing microaspiration. 91 Use of specialized ETTs may be of particular benefit in trauma and acute brain injury patients.…”
Section: Modifiable Risk Factors For Ventilator-associated Pneumonia mentioning
confidence: 99%
“…Based on literatures, advanced age, obesity, cigarette smokers, American Society of Anesthesiologist (ASA) physical status of>II, chronic obstructive pulmonary disease (COPD), low albumin level, upper abdominal and thoracic surgery, prolonged surgical and anesthesia time [10,11], general anesthesia with long acting muscle relaxant [12] and type of endotracheal tube [13] are the identified risk factors for postoperative pulmonary complications.…”
Section: Introductionmentioning
confidence: 99%